Visible Japanese and Invisible Filipino Narratives of the Development of Davao, 1900s to 1930s - Patricia Irene Dacudao, Lydia N. (Archīum Ateneo, 2015)
Although the southern Philippine province of Davao had the largest number of Japanese inhabitants in Southeast Asia before the Second World War, the Japanese in Davao were a minority compared with the Filipino settlers there. Nonetheless, the literature has focused predominantly on the role of the Japanese in the development of Davao’s abaca (Manila hemp) industry and, by extension, the development of Davao itself during the period of American colonial rule. Thisarticle seeks to explain, given this predominant focus on the Japanese, the relative invisibility of Filipinos in the narratives of Davao’s development during the period of the 1900s to the 1930s.KEYWORDS: DAVAO • MINDANAO • FILIPINO SETTLERS • JAPANESE MIGRANTS • ABACA